2016
DOI: 10.17507/tpls.0607.04
|View full text |Cite
|
Sign up to set email alerts
|

Bangladeshi EFL Learners’ English Connectors: Overused or Underused?

Abstract: Abstract-The paper investigates the answer scripts of an "English Writing" exam of 72 students in a Bangladeshi university in order to find out the nature and extent of the use of connectors in their second semester-final exam. It also tries to find out similarities and differences between the connector use of Bangladeshi non-native speakers (BNNS) and that of French, Japanese, Swedish, and Chinese non-native speakers on the one hand and between the connector use of BNNS and that of the native speakers of Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…In a study by Faruk and Barua (2016), students' connective use was analyzed by category for ELs. Results indicated that most common connectors were used among and between language groups.…”
Section: Students From Diverse Linguistic and Ability Backgroundsmentioning
confidence: 99%
“…In a study by Faruk and Barua (2016), students' connective use was analyzed by category for ELs. Results indicated that most common connectors were used among and between language groups.…”
Section: Students From Diverse Linguistic and Ability Backgroundsmentioning
confidence: 99%